A retrospective, multicentric, nationwide analysis of the impact of splenectomy on survival of pancreatic cancer patients: research - Kießler, Maximilian; Jäger, Carsten; Mota Reyes, Carmen; Pergolini, Ilaria; Schorn, Stephan; Göß, Rüdiger; Safak, Okan; Martignoni, Marc E.; Novotny, Alexander R.; Uhl, Waldemar; Werner, Jens; Ghadimi, Michael; et al. (Langenbeck's archives of surgery, 2025)
Objective Splenectomy is regularly performed in total and distal pancreatectomy due to technical reasons, lymph node dissection and radicality of the operation. However, the spleen serves as an important organ for competent immune function, and its removal is associated with an increased incidence of cancer and a worse outcome in some cancer entities (Haematologica 99:392-398, 2014; Dis Colon Rectum 51:213-217, 2008; Dis Esophagus 21:334-339, 2008). The impact of splenectomy in pancreatic cancer is not fully resolved (J Am Coll Surg 188:516-521, 1999; J Surg Oncol 119:784-793, 2019). Methods We therefore compared the outcome of 193 pancreatic cancer patients who underwent total or distal pancreatectomy with (Sp) or without splenectomy (NoSp) between 2015 and 2021 using the StuDoQ|Pancreas registry of the German Society for General and Visceral Surgery. In addition, we integrated our data into the existing literature in a meta-analysis of studies on splenectomy in pancreatic cancer patients. Results There was no difference between the Sp and NoSp groups regarding histopathological parameters, number of examined or affected lymph nodes, residual tumor status, or postoperative morbidity and mortality. We observed a significantly prolonged survival in pancreatic cancer patients who underwent total pancreatectomy, when a spleen-preserving operation was performed (median survival: 9.6 vs. 17.3 months, p = 0.03). In this group, splenectomy was identified as an independent risk factor for shorter overall survival [HR (95%CI): 2.38 (1.03 - 6.8)]. In a meta-analysis of the existing literature in combination with our data, we confirmed splenectomy as a risk factor for a shorter overall survival in pancreatic cancer patients undergoing total pancreatectomy, distal pancreatectomy, or pancreatic head resection [HR (95%CI): 1.53 (1.11 - 1.95)]. Conclusion Here, we report on a strong correlations between removal of the spleen and the survival of pancreatic cancer patients undergoing total pancreatectomy. This should encourage pancreatic surgeons to critically assess the role of splenectomy in total pancreatectomy and give rise to further investigations.